Efficacy and safety of laser therapy on axillary hyperhidrosis after one year follow‐up: A randomized blinded controlled trial. Issue 2 (6th February 2015) - Leclère, Franck Marie; Moreno‐Moraga, Javier; Alcolea, Justo M.; Vogt, Peter M.; Royo, Josefina; Cornejo, Paloma; Casoli, Vincent; Mordon, Serge; Trelles, Mario A.; Avram, Mathew M.; Ortiz, Arisa E.
<x xml:space="preserve">Abstract</x> Introduction Hyperhidrosis is a debilitating problem that is not only uncomfortable and inconvenient, but also embarrassing in work and social situations. In spite of the availability of several options for the treatment of axillary hyperhidrosis, recently, there has been an increasing interest in the use of laser therapy. This study aims to evaluate the efficacy of a laser diode device emitting at wavelengths of 924 and 975 nm and classical curettage either alone, simultaneously or in combination. Material and methods A randomized prospective controlled trial was carried out on 100 patients divided into four groups, each with a different protocol: Laser alone at 975 nm (group 1), laser alone at 924/975 nm simultaneously (group 2), curettage alone (group 3), and finally laser at 924/975 nm followed by curettage (group 4). HDSS, starch test and GAIS were used to assess treatment efficacy. The follow‐up extended to one year. Statistical analysis (SPSS) was used to determine the accuracy of the results. Result Two patients of group 1 experienced burns during treatment, which took over a month to heal. This group of patients achieved the worst results: The starch test scale results after treatment were 2.48 ± 0.51 and 2.76 ± 0.44 (at 1 and 12 months). The GAIS results were 1.04 ± 0.35 and 0.92 ± 0.28 (1 and 12 months). In group 2 the starch test scale results after treatment were 1.36 ± 0.49 and 1.48 ± 0.51 (at 1 and 12 months). The GAIS results were 2.36 ± 0.49 and 2.72 ± 0.46 (at 1 and 12 months). In group 3, the starch test scale results after treatment were 1.56 ± 0.51 and 1.76 ± 0.60 (at 1 and 12 months), which corresponds to small to substantially smaller dark areas. The GAIS results were 2.28 ± 0.46 and 2.64 ± 0.49 (at 1 and 12 months). The best results were obtained in group 4: HDSS scores were reduced from 3.88 ± 0.33 before treatment to 1.24 ± 0.44 and 0.48 ± 0.51 at the 1 and 12 months controls. The starch test scale results after treatment were 0.40 ± 0.50 and 0.44 ± 0.51 (at 1 and 12 months). The GAIS results were 3.72 ± 0.54 and 3.76 ± 0.44 (at 1 and 12 months). Conclusion In this study, the laser at 924/975 nm combined with curettage was determined to be the optimal treatment option of those tested for axillary hyperhidrosis. This treatment was safe, with few side effects and improvement that persisted to one year follow‐up. Lasers Surg. Med. 47:173–179, 2015. © 2015 Wiley Periodicals, Inc.